AVEREL: a randomized phase III Trial evaluating bevacizumab in combination with docetaxel and trastuzumab as first-line therapy for HER2-positive locally recurrent/metastatic breast cancer - Gianni, Luca; Romieu, Gilles H; Lichinitser, Michail; Serrano, Sergio V; Mansutti, Mauro; Pivot, Xavier; Mariani, Paola; Andre, Fabrice; Chan, Arlene; Lipatov, Oleg; Chan, Stephen; Wardley, Andrew; et al. (Journal of clinical oncology, 2013)
PURPOSE The AVEREL trial [A Study of Avastin (Bevacizumab) in Combination With Herceptin (Trastuzumab)/Docetaxel in Patients With HER2-Positive Metastatic Breast Cancer] evaluated first-line bevacizumab-containing therapy for human epidermal growth factor receptor 2 (HER2) -positive locally recurrent/metastatic breast cancer (LR/MBC). PATIENTS AND METHODS Patients with measurable/evaluable HER2-positive LR/MBC who had not received trastuzumab or chemotherapy for LR/MBC were stratified by prior adjuvant trastuzumab, prior (neo)adjuvant taxane, hormone receptor status, and measurable disease and were randomly assigned to receive docetaxel 100 mg/m(2) plus trastuzumab 8 mg/kg loading dose followed by 6 mg/kg either with bevacizumab 15 mg/kg or without bevacizumab, all administered every 3 weeks. The primary end point was progression-free survival (PFS). Additional end points included overall survival, response rate (RR), safety, quality of life, and translational research. Results Baseline characteristics of the 424 patients were balanced between treatment arms. Most patients had visceral metastases, 43% had a disease-free interval less than 12 months, and 85% had measurable disease. Median follow-up was 26 months. The hazard ratio for investigator-assessed PFS was 0.82 (95% CI, 0.65 to 1.02; P = .0775; median PFS, 13.7 v 16.5 months in the non-bevacizumab and bevacizumab arms, respectively; PFS events in 72%). The Independent Review Committee-assessed PFS hazard ratio was 0.72 (95% CI, 0.54 to 0.94; P = .0162; median PFS, 13.9 v 16.8 months, respectively; PFS events in 53%). The RR was 70% versus 74%, respectively (P = .3492). Grade ≥ 3 febrile neutropenia and hypertension were more common with bevacizumab-containing therapy. High baseline plasma vascular endothelial growth factor A (VEGF-A) concentrations were associated with greater bevacizumab benefit (not statistically significant). CONCLUSION Combining bevacizumab with docetaxel and trastuzumab did not significantly improve investigator-assessed PFS. The potential predictive value of plasma VEGF-A is consistent with findings in HER2-negative LR/MBC, warranting prospective evaluation.